2015
DOI: 10.1007/s10578-015-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the German Version of the Child Post-Traumatic Cognitions Inventory (CPTCI-GER)

Abstract: Dysfunctional trauma-related cognitions are associated with posttraumatic stress disorder (PTSD). The psychometric properties of the German version of the Child Post-Traumatic Cognitions Inventory (CPTCI-GER) were assessed in a sample of 223 children and adolescents (7–16 years) with a history of different traumatic events. Confirmatory factor analyses supported the original two-factor structure—permanent and disturbing change (CPTCI-PC) and fragile person in a scary world (CPTCI-SW). The total scale and both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The German version of the CPTCI [26] has good reliability (α = 0.94) and convergent validity with standard measures of PTSS and depression. In the current study Cronbach's α was 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…The German version of the CPTCI [26] has good reliability (α = 0.94) and convergent validity with standard measures of PTSS and depression. In the current study Cronbach's α was 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…Example items are, as mentioned earlier, “My reactions since the frightening event mean I have changed for the worse” (CPTCI‐PC) and “I can't stop bad things from happening to me” (CPTC‐SW item). The German version has demonstrated good psychometric properties in regards to both the total scale (Cronbach's α = .94) and subscales (Cronbach's αs = .91 for the CPTCI‐PC and .86 for the CPTCI‐SW; de Haan, Petermann, Meiser‐Stedman, & Goldbeck, ). At each time point, the subscales were highly correlated with the total score, Spearman's ρ = .91–.96, p s < .001, as well as highly intercorrelated, Spearman's correlations = .76–.79, p s < .001, in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…The CPTCI has been translated into several languages, and different versions have been validated and their psychometric properties have been reported in Germany [ 22 ], the Netherlands [ 17 ], Brazil [ 23 ] and Taiwan [ 24 ]. Previous studies generally report adequate levels of reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in all these samples the two-factor structure emerged as the best solution. These studies, however, showed that the original two-factor structure of CPTCI exhibits unsatisfactory model fit indices that do not meet the widely accepted criteria [ 17 , 21 , 22 , 24 , 25 ]. Authors attribute these discrepancies to sample characteristics and cultural differences.…”
Section: Introductionmentioning
confidence: 99%